Design of a Multi-Tenant Database for a Village Water Management Information System (Nusa Tirta) - aulia; Dinar Mustofa; Rizki Cahya Putri; Intan Nur Sifa; Mayza Nurul Khasanatun Nisa; Purnia Setiawati; Sri Rahayu; Lina Nur Afifah (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Village water management through BUMDes often faces challenges due to inefficiency resulting from the use of a recording system that is still manual, prone to errors and lacks transparency. This study aims to design a structured database for the "Nusa Tirta" system to support the digitization process of village clean water management. The research method used is a qualitative approach combining literature review and case study to test the Entity Relationship Diagram (ERD) structure through the application of a multi-tenant schema. The results indicate that the implementation of a shared schema architecture with the tenant_id attribute can securely maintain data separation between villages within a single integrated system. The use of integrity constraints and automatic relationships between tables also helps reduce the risk of human error and improves the accuracy of transaction data. Thus, this design can serve as the foundation for the development of a more flexible and secure village digital system that supports improvements in operational services in the future.